NILAI BUDAYA DAN PELESTARIAN TARI BABANGSAI DI MASYARAKAT DAYAK MARATUS LOKSADO - Elin, Sepringga; Edi, Sutardi; Rahmani, Rahmani (Universitas Negeri Makassar, 2024)
In the traditional ritual ceremony activities of the Loksado village community, there is a dance which has a role/function as one of the many communication media in expressing gratitude and expression of respect for the creator referred to in the ritual ceremony activities. The Babangsai dance is presented as an inseparable part of the Mahanyari Banih and Aruh Ganal ceremonies. This research aims to (1) Describe the form of presentation of the Babangsai dance in the Dayak Meratus Loksado community. (2). Describe the cultural values contained in the Babangsai dance of the Dayak Meratus Loksado community. (3). Describe efforts to preserve the Babangsai dance in the Dayak Meratus Loksado Community The research uses qualitative methods, the data collection techniques used are observation and interviews with several sources who are interested in the research, as well as documentation in the form of videos or photos which serve as supporting evidence for the research.Based on the research results obtained in the form of observations, it shows that (1). The form of presentation of the Babangsai dance in the Dayak Meratus Loksado community has the beauty of simple movements, but is more concerned with the purpose of conveying message/wishes to Sang Hiyang Bahatara and to summon spirits. Ancestors. (2). The cultural values contained in the Babangsai dance in traditional aruh ceremonies depict a from of expression of gratitude, worship of a successful rice harvest to produce abundant rice. This activity provides an attitude of gratitude, mutual cooperation, unity and social valuse among residents.(3). The obstacle in preserving the Babangsai dance in Loksado District is the lack of management and training for the Babangsai dance, the lack of interest and enthysiasm among the younger generation of Loksado to dance this dance.